2019
DOI: 10.1002/mrd.23237
|View full text |Cite
|
Sign up to set email alerts
|

Mutation ofcyp19a1bresults in sterile males due to efferent duct obstruction in Nile tilapia

Abstract: The involvement of estrogen in male fertility has been well established in mammals. However, less is known about the role of estrogen in fish male reproduction. Our recent study revealed that Cyp19a1a deficiency had no effect on fertility in male fish. In this study, expression of Cyp19a1b, but not Cyp19a1a, was detected by immunohistochemistry in Leydig cells of tilapia testes. cyp19a1b mutation resulted in a significant decrease in the concentration of 17β‐estradiol in serum and sterility in XY fish, as no o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 59 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…As is well known, the efferent duct is responsible for the absorption of fluid from the lumen, spermatozoon maturation, spermiophagy, and secretion of steroid hormone [31,32,33]. Recent studies reported that the male sterility caused by the mutation of either Nile tilapia Cyp19a1b or mouse Gemc1 is primarily due to the defect of efferent duct development [34,35]. Thus, further work will be needed to clarify the roles of both Sox30 and Dmrt1 in the efferent duct of the Nile tilapia testis.…”
Section: Discussionmentioning
confidence: 99%
“…As is well known, the efferent duct is responsible for the absorption of fluid from the lumen, spermatozoon maturation, spermiophagy, and secretion of steroid hormone [31,32,33]. Recent studies reported that the male sterility caused by the mutation of either Nile tilapia Cyp19a1b or mouse Gemc1 is primarily due to the defect of efferent duct development [34,35]. Thus, further work will be needed to clarify the roles of both Sox30 and Dmrt1 in the efferent duct of the Nile tilapia testis.…”
Section: Discussionmentioning
confidence: 99%
“…In tilapia ( Oreochromis niloticus ), depletion of cyp19a1b has been reported to cause male infertility due to efferent duct obstruction (17). If this is also the case in medaka, the observed behavioral defects might be secondary to infertility.…”
Section: Resultsmentioning
confidence: 99%
“…The XX and XY heterozygotes for amhy , dmrt1 , gsdf , cyp19a1a , cyp19a1b and foxl3 alleles were previously generated by CRISPR/Cas9 [ 9 , 12 14 , 42 , 43 ]. These mutant lines were maintained in our laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…The gsdf -/- ; cyp19a1a -/- ; cyp19a1b -/- triple mutants cannot be obtained by crossing using gsdf + /- ; cyp19a1a + /- double heterozygotes and cyp19a1b + /- heterozygotes. In our previous study, the cyp19a1b was efficiently targeted by CRISPR/Cas9 [ 42 ]. For generation of gsdf -/- ; cyp19a1a -/- ; cyp19a1b -/- triple mutants, the gRNA for cyp19a1b was in vitro transcription with T7 RNA polymerase followed by purification with QIAquick PCR Purification Kit (QIAGEN, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation